Genetic Background Effects on the Expression of an Odorant Receptor Gene - Leme Silva, Artur Guazzelli; Nagai, Maira Harume; Nakahara, Thiago Seike; Malnic, Bettina (Frontiers in Cellular Neuroscience, 2021)
There are more than 1000 odorant receptor (OR) genes in the mouse genome. Each olfactory sensory neuron expresses only one of these genes, in a monoallelic fashion. The transcript abundance of homologous OR genes vary between distinct mouse strains. Here we analyzed the expression of the OR gene Olfr17 (also named P2) in different genomic contexts. Olfr17 is expressed at higher levels in the olfactory epithelium from 129 mice than from C57BL/6 (B6) mice. However, we found that in P2-IRES-tauGFP knock-in mice, the transcript levels of the 129 Olfr17 allele are highly reduced when compared to the B6 Olfr17 allele. To address the mechanisms involved in this variation we compared the 5′ region sequence and DNA methylation patterns of the B6 and 129 Olfr17 alleles. Our results show that genetic variations in cis regulatory regions can lead to differential DNA methylation frequencies in these OR gene alleles. They also show that expression of the Olfr17 alleles is largely affected by the genetic background, and suggest that in knock-in mice, expression can be affected by epigenetic modifications in the region of the targeted locus.